Electrochemical recovery of minor concentrations of gold from cyanide-free cupric chloride leaching solutions. (10th June 2018) - Korolev, Ivan; Altınkaya, Pelin; Halli, Petteri; Hannula, Pyry-Mikko; Yliniemi, Kirsi; Lundström, Mari
Abstract: Despite of being the most common hydrometallurgical process for extraction of gold from ores and concentrates, cyanide leaching is blamed for its hazardous impact on environment and human health. These concerns have given a rise for alternative cyanide-free technologies, such as cupric chloride leaching. However, the state-of-art processes for gold recovery from chloride solutions are facing issues of high reagent consumption and poor selectivity. This article describes an innovative method for recovery of minor concentrations of gold from hydrometallurgical solutions by repetitive Electrochemical Deposition-Redox Replacement (EDRR) cycles. In contrast to conventional carbon-in-leach/resin-in-leach technologies or solvent extraction, the proposed electrochemical method does not require addition of any chemicals in the process and remarkably selective gold recovery can be achieved from concentrated cupric solution by tailoring the process parameters. A number of electrochemical experiments was performed in order to identify the process variables affecting the Au recovery. Results indicate that so called cut-off potential and deposition time were the EDRR parameters having the strongest impact on gold recovery at fixed concentration of Cu and Au ions. The Au content in the metal deposit after 250 EDRR cycles exceeded 75% and the Au:Cu ratio has increased by a factor of 1000, from 1:340 in the solution up to 3.3:1 in the final product. X-ray photoelectron spectroscopy analysis of the cathode surface confirmed full replacement of sacrificial copper with gold. Obtained results prove that the EDRR method can be efficiently used for the recovery of trace amounts of gold from cupric chloride solutions used for cyanide-free gold leaching. Graphical abstract: Image 1 Highlights: A novel process for gold recovery from chloride leaching solutions is proposed. The method uses spontaneous redox replacement reactions between gold and copper. No chemical addition is required to obtain high selectivity of the process. Concentration of gold in final product increased 1000 times compared to initial.